2020
DOI: 10.1073/pnas.2007827117
|View full text |Cite
|
Sign up to set email alerts
|

Daily mitochondrial dynamics in cone photoreceptors

Abstract: Cone photoreceptors in the retina are exposed to intense daylight and have higher energy demands in darkness. Cones produce energy using a large cluster of mitochondria. Mitochondria are susceptible to oxidative damage, and healthy mitochondrial populations are maintained by regular turnover. Daily cycles of light exposure and energy consumption suggest that mitochondrial turnover is important for cone health. We investigated the three-dimensional (3D) ultrastructure and metabolic function of zebrafish cone mi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 113 publications
6
26
0
Order By: Relevance
“…Our observations of mitochondrial expulsion of electron-dense aggregates from the photoreceptor are broadly in agreement with those described in zebra sh 42 . In this elegant paper the authors refer to similar structures they identi ed in mouse.…”
Section: Discussionsupporting
confidence: 91%
“…Our observations of mitochondrial expulsion of electron-dense aggregates from the photoreceptor are broadly in agreement with those described in zebra sh 42 . In this elegant paper the authors refer to similar structures they identi ed in mouse.…”
Section: Discussionsupporting
confidence: 91%
“…Our observations of mitochondrial expulsion of electron-dense aggregates from the photoreceptor are broadly in agreement with those described in zebrafish 41 . In this elegant paper the authors refer to similar structures they identified in mouse.…”
Section: Discussionsupporting
confidence: 91%
“…Extraction of RNA, cDNA synthesis, and qRT-PCR amplification were conducted, as previously described using TATA-box binding protein as a reference gene ( 37 , 60 ). The primers are listed in Table 1 .…”
Section: Methodsmentioning
confidence: 99%